EEG CHANGES IN MIGRAINE PATIENTS - TAPASWINI MISHRA; DIPTI MOHAPATRA; MANASI BEHERA; NIBEDITA PRIYADARSINI (International Journal of Pharma and Bio Sciences, 2015)
Migraine is a common, debilitating disorder that imposes a large personal burden on sufferers and high economic costs on society. Sufferers have a significant level of migraine related disability in all aspects of their daily lives, including employment, household work and non-work activities. Since there is a wide range of disorders that cause headache, a systematic approach to classification and diagnosis is an essential prelude to clinical management and to useful research. The EEG is frequently used in the examination of patients with migraine now days.